Efficacy and Safety of Transcatheter Tricuspid Valve Replacement in Patients With Moderate to Severe Tricuspid Regurgitation: A Systematic Review and Meta‐Analysis on Clinical Outcomes and Echocardiographic Indices - Pouria Azami; Alireza Hosseinpour; Jahangir Kamalpour; Farshad Rajabi; Iman Razeghian‐Jahromi; Sarvenaz Farhangdoost; Reza Golchin Vafa; Ghazaleh Bagheri (Health Science Reports)
ABSTRACT Background and Aims Tricuspid regurgitation (TR) is a prevalent, often overlooked condition linked to significant morbidity and mortality in older adults. Due to the high risks associated with conventional surgery, transcatheter tricuspid valve replacement (TTVR) has emerged as a less invasive alternative. This systematic review and meta‐analysis evaluated the clinical outcomes and echocardiographic indices of TTVR. Methods Five databases were searched systematically, and eligible studies included patients with moderate or severe TR who underwent TTVR. Risk of bias was assessed using the ROBINS‐I tool for observational studies and the JBI checklist for case series. A random‐effects meta‐analysis was performed to evaluate the impact of TTVR on major adverse cardiovascular events (MACE) and echocardiographic parameters. Results Twenty‐one studies with 643 patients (mean age 75.8 years, 70.76% female) reported a 94% technical success rate for TTVR (95% CI: 91–96%). 30‐day mortality was 4% (95% CI: 2–6%) and 1‐year mortality was 9% (95% CI: 6%–13%). Significant improvements were noted in TR severity (OR = 0.0013, 95% CI: 0.0006–0.0027, p < 0.001) and PASP (MD = −8.69 mmHg, 95% CI: −11.54 to −5.84, p < 0.001), along with reductions in right ventricular base diameter (MD = −6.33 mm, 95% CI: −8.92 to −3.75, p < 0.001) and RV end‐diastolic mid diameter (MD = −6.33 mm; 95% CI [−8.18, −5.52]; p < 0.001; I² = 5%). Conclusion TTVR presents a promising treatment alternative for high‐risk patients with severe TR, demonstrating high technical success, favorable clinical outcomes, and significant echocardiographic improvements. While the procedure is associated with low in‐hospital and 1‐year mortality, further studies are needed to evaluate long‐term outcomes and optimize patient selection for this emerging therapy.